Are there disadvantaged clienteles in mutual funds? - Stephan Jank (University of Cologne, Centre for Financial Research (CFR), 2011)
This paper studies the flow-performance relationship of three different investor groups in mutual funds: Households, financial corporations, and insurance companies and pension funds, establishing the following findings: Financial corporations have a strong tendency to chase past performance and also hold an increased share in the top performing funds. Insurance companies and pension funds show some evidence of performance chasing, but are underrepresented in the best performing funds. Households chase performance, but they are also subject to status quo bias in their flows. Regarding investor composition the worst performing funds show no significant difference in their investor structure when compared to funds with average performance.
Keywords: G11; G20; G23; 330; Mutual Funds; Flow-Performance Relationship; Clientele